위험과 정보의 불확실성이 서비스품질 평가에 미치는 영향에 관한 연구 - 암환자를 중심으로 - - 윤인희 (The Graduate School, Ajou University, 2013)
Hospitals tend to provide uniform service to patients despite their various demands they may have due to the risks of disease stages or the uncertainties in terms of information of treatment stages. To identify service factors that patients consider to be important depending on their individual circumstances and provide effective contextual service models for different service needs, the study conducted a survey on the importance of and the satisfaction with service quality. The study surveyed 286 patients and caregivers on importance and satisfaction regarding 17 service factors at the outpatient clinic of cancer centers at the university hospitals in 5 major cities in Korea. Based on the risks of the disease and uncertainties in terms of information of treatment stages, the cancer patients were grouped into 4 categories; diagnosis stage, low-risk treatment stage, high-risk treatment stage and stabilization stage. This study revealed that there are significant differences in terms of satisfaction with different service factors depending on cancer patients’ cases. Depending on the patient’s situation, the importance of and satisfaction with service factors were ranked. These factors were categorized into 4 groups from a managerial perspective; ‘keep it up’, ‘focus here’, ‘low priority’ and ‘overdone’. Thus, this study provides an effective healthcare service model that can accommodate different service needs of patients.
학위논문(박사)아주대학교 일반대학원 :경영학과,2013. 2
Keywords: healthcare service factors; conditions and circumstances of cancer patients; contextual service model